Managing Conflict among Teachers: A Systematic Literature Review Framework for Enhancing Educational Service Quality in Indonesia - Tutty Rokhayati Rosa, Ade; Edwar Setiawan; Mardiyati, Mardiyati; Nahdiah, Indah (Al-Qalam Institue, 2025)
This study presents a systematic review of existing literature on teacher conflict management through a systemic approach to enhance the quality of educational services. Utilizing the Systematic Literature Review (SLR) method, 22 nationally accredited journal articles published between 2020 and 2024 were identified, from which 5 articles were selected based on relevance, methodological rigor, and contextual alignment. The findings indicate that teacher conflicts are predominantly triggered by ineffective communication, non-inclusive leadership practices, and misalignments in organizational values and culture. Conflict resolution strategies identified include internal mediation, conflict management training, collaborative leadership, and the reinforcement of value-based organizational norms. The systemic approach offers a comprehensive lens to analyze the interrelated organizational, interpersonal, and cultural dimensions influencing conflict dynamics. This review contributes conceptually to the development of an integrated model for teacher conflict resolution tailored to the socio-cultural realities of Indonesian educational institutions. Furthermore, it highlights the need for future research to combine contemporary conflict management theories with local religious and cultural frameworks in order to support sustainable, collaborative school environments, especially in the context of the Society 5.0 era.